Longitudinal Trends of Financial Toxicity in Patients With Lung Cancer: A Prospective Cohort Study. Issue 8 (August 2021) - Friedes, Cole; Hazell, Sarah Z.; Fu, Wei; Hu, Chen; Voong, Ranh K.; Lee, Beverly; Feliciano, Josephine L.; Nicholas, Lauren H.; McNutt, Todd R.; Han, Peijin; Narang, Amol K.; Hales, Russell K.
Abstract : BACKGROUND: Cancer therapy is associated with severe financial burden. However, the magnitude and longitudinal patient relationship with financial toxicity (FT) in the initial course of therapy is unclear. METHODS: Patients with stage II-IV lung cancer were recruited in a prospective longitudinal study between July 2018 and March 2020. FT was measured via the validated COmprehensive Score for financial Toxicity (COST) at the time of cancer diagnosis and at 6-month follow-up (6MFU). 6MFU data were compared with corresponding baseline data. A lower COST score indicates increased financial hardship. RESULTS: At the time of analysis, 215 agreed to participate. Subsequently, 112 patients completed 6MFU. On average, slightly more FT was observed at diagnosis compared with 6MFU (median COSTbase 25 v COST6M 27; P < .001); however, individual patients experienced large changes in FT. At 6MFU, 27.7% of patients had made financial sacrifices to pay for treatment but only 4.5% refused medical care based on cost. Median reported out-of-pocket (OOP) costs for the initial 6 months of cancer treatment was $2, 496 (range, $0-25, 900). Risk factors for FT at diagnosis were unique from risk factors at 6MFU. Actual OOP expenses were not correlated with FT; however, inability to predict upcoming treatment expenses resulted in higher FT at 6MFU. DISCUSSION: FT is a pervasive challenge during the initiation of lung cancer treatment. Few patients are willing to sacrifice medical care regardless of the cost. Risk factors for FT evolve, resulting in unique interventional targets throughout therapy.